PEMEROLEHAN FONOLOGI PADA ANAK USIA 3 TAHUN - Andriani, Rina; Saputra, Desma Yuliadi; Angraeni, Wati (Jurnal Anak Bangsa, 2025)
The acquisition of phonology is obtained from an early age and is the starting point for children to communicate. The development of phonology acquisition is very important to be carried out in order to detect language (speaking) disorders in children as well as to find out the extent of children's development. This study is related to finding out and analyzing the acquisition of language of 3-year-old children from the aspect of phonology, including the acquisition of vowels, consonants, and other factors that affect the acquisition of phonology. The object of the research was a 3-year-old child named Khalista. This study uses a descriptive qualitative method with naturalistic data collection techniques used to collect data, namely recording conversations by interacting directly, listening, and conversing and then the data obtained in the form of recordings is transcribed into writing. Based on the results of the study, that the acquisition of phonology in the form of vowels has been well mastered, but phonemic pronunciation and decapitation of syllables are still found, so that eliminating letters or language sounds in spoken words will change the sound of language. Language acquisition in children is influenced by environmental, biological, and developmental age factors.